2020
DOI: 10.3390/su12187747
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Carbon Emissions, Energy Use, Economic Growth and Financial Development: Evidence from Central and Eastern European Countries

Abstract: The aim and novelty of this study consist of estimating the nexus between CO2 (carbon dioxide) emissions, energy use, economic growth, and financial development for ten Central and Eastern European countries (CEEC) over the 2000–2017 period, starting from Environmental Kuznets Curve (EKC) theory. The Fully Modified Ordinary Least Squares (FMOLS) method was used for testing the cointegration relationship. Granger causality estimation based on the Vector Error Correction Model (VECM) and Pairwise Granger causali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Empirical studies also suggest negative significant outcome between financial development and CO2 emissions in Malaysia and Singapore which is consistent in the long-and short-run. The result also conforms with Manta et al (2020) who observed that a country that cares of a clean environment will always strive to spend towards the reduction of CO2 emissions gases. This consistency will eventually lead the country to achieve pollution-free status in the long-run.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Empirical studies also suggest negative significant outcome between financial development and CO2 emissions in Malaysia and Singapore which is consistent in the long-and short-run. The result also conforms with Manta et al (2020) who observed that a country that cares of a clean environment will always strive to spend towards the reduction of CO2 emissions gases. This consistency will eventually lead the country to achieve pollution-free status in the long-run.…”
Section: Discussionsupporting
confidence: 89%
“…Most past studies have adopted the cross-sectional or panel data techniques (Martínez-Zarzoso et al 2011;Manta et al 2020; among others studies) to estimate the relationship between CO2 emissions and various macroeconomics indicator including gross domestic product, urbanization and energy consumption. But, from econometrics perspective, some of the studies gave arguments favorable to the EKC hypothesis, yet it was not confirmed whether any particular country sampled will follow the same pollution path estimated for the panel of countries (Fodha & Zaghdoud 2010;Chebbi et al 2011;among others studies).…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The linkage of CO 2 emissions between energy use, economic growth, and financial development applied to CEEC countries for 2000-2017 was investigated by Manta et al (2020) using FMOLS, VECM, and Pairwise Granger causality test. The results demonstrated that there exists bidirectional causality between income per capita and financial system development.…”
Section: Economic Growth and Environmentmentioning
confidence: 99%
“…However no long-run relation in Sweden, Norway, Luxemburg, Motherland, UK, France, Belgium, Finland Austria. Manta et al, (2020) estimated the nexus among CO2 emission, economic growth, energy use, and financial development in Central and Eastern European Countries (CEEC) using VECM and Granger causality over the period of 2000 to 2017. The result shows that in the long run energy emission and CO2 emission have no impact on economic growth while in the short run increasing financial development increases the CO2 emission and leads to enhanced economic growth.…”
Section: Economic Growth and Environmental Pollutionmentioning
confidence: 99%